2002
DOI: 10.5194/angeo-20-1181-2002
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous ionospheric global conductance maps during an isolated substorm

Abstract: Abstract. Data from the Polar Ionospheric X-ray Imager (PIXIE) and the Ultraviolet Imager (UVI) on board the Polar satellite have been used to provide instantaneous global conductance maps. In this study, we focus on an isolated substorm event occurring on 31 July 1997. From the PIXIE and the UVI measurements, the energy spectrum of the precipitating electrons can be derived. By using a model of the upper atmosphere, the resulting conductivity values are generated. We present global maps of how the 5 min timea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…The temporal resolution of the UVI conductance estimate (the time required to take both LBHS and LBHL images) is 184 s for this specific event. Aksnes et al (2002) have shown that conductance estimates derived from only UVI data may underestimate the Hall conductance by several tens of percent. This is caused by the limited sensitivity to precipitating electrons with energies over 20 keV, which contribute to the Hall conductance.…”
Section: Uvi Conductance Estimatesmentioning
confidence: 99%
“…The temporal resolution of the UVI conductance estimate (the time required to take both LBHS and LBHL images) is 184 s for this specific event. Aksnes et al (2002) have shown that conductance estimates derived from only UVI data may underestimate the Hall conductance by several tens of percent. This is caused by the limited sensitivity to precipitating electrons with energies over 20 keV, which contribute to the Hall conductance.…”
Section: Uvi Conductance Estimatesmentioning
confidence: 99%
“…During the recovery phase, PIXIE showed a precipitation maximum in the morning sector which was not seen by UVI. Many studies have reported such a maximum in the energetic electron precipitation in the dawn region, including substorm studies (Jelly and Brice, 1967;Berkey et al, 1974;Østgaard et al, 2001;Aksnes et al, 2002) and statistical studies involving different geomagnetic conditions (Hartz and Brice, 1967;McDiarmid et al, 1975;Wallis and Budzinski, 1981;Spiro et al, 1982;Hardy et al, 1985;Hardy et al, 1987). Østgaard et al (1999) used models of the gradient and curvature drift of electrons to estimate the energy of eastward drifting electrons causing the X-rays seen by PIXIE.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Aksnes et al (2002) showed that the calculation of an accurate Hall conductance depends strongly on measurements of energetic electrons up to 100 keV. Aksnes et al (2002) also used Polar data from the PIXIE and UVI cameras, in order to provide instantaneous global conductance maps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the rapid changes with time it is speculated whether the 630 nm line is a good observable in this case. This atomic oxygen line is an emission from a forbidden transition from the metastable O( 1 D) state which has a lifetime of about 100 s. The spectral information is, therefore, also obtained from riometer and 427.8 nm photometer data using an extended version (a description is given by Aksnes et al, 2002) of an original model developed by Vondrak and Baron (1976) and validated by Vondrak and Sears (1978). The model is based on the techniques described by Rees (1963).…”
Section: Electron Energy Spectrummentioning
confidence: 99%